Foot pressure profile for the paretic and non-paretic lower extremities in children with spastic hemiplegic cerebral palsy and the relationship with postural stability. Cross-sectional study - Alruwaili, Atheer; Ibrahim, Alaa; Abualait, Turki (Acta Biomedica Atenei Parmensis, 2025)
Background: Cerebral palsy is a nonprogressive neurodevelopmental disorder that causes motor impairments and limb asymmetries in children with hemiplegic CP, leading to altered plantar pressure, reduced postural stability, and functional gait limitations. Aim: This study compared foot pressure profiles between paretic and non-paretic limbs in children with hemiplegic cerebral palsy and controls and examined their relationship with postural stability. Methods: In this cross-sectional study, 20 children with HCP (mean age: 8.1±1.65 years) and 31 TD (mean age: 8.06±1.15 years) underwent spasticity assessment using the Modified Ashworth Scale. Static plantar pressures were measured with the DIERS Pedoscan system, while dynamic PS indices were recorded using the TecnoBody device under eyes-open and closed conditions. Results: Within the HCP group, affected feet demonstrated significantly lower maximum and average pressures, pressure distribution, surface area, and hindfoot pressure compared to non-affected feet (all p≤0.019). Compared to controls, children with HCP showed significantly greater limb length discrepancies (p<0.001) and poorer Overall Stability Index (OSI) scores at level 10 under both eyes-open (p=0.015) and eyes-closed (p=0.005) conditions. Correlation analyses revealed that higher body weight (r=0.559; p=0.014) and BMI (r=0.548; p<0.015) were positively associated with increased symmetry of the foot axis angle. In contrast, greater foot length differences (r=–0.528; p<0.017) were associated with reduced symmetry in maximum hindfoot pressure. Regression analysis identified leg length difference (B=0.50, p=0.04) and OSI at stability level 10 with eyes closed (B=0.17, p=0.47) as significant predictors of the symmetry index for anteroposterior and mediolateral foot movements in HCP children. Conclusion: Children with HCP show notable foot pressure asymmetries, reduced hindfoot support, and poorer postural stability, influenced by limb length differences, body weight, and BMI. Leg length discrepancy and eyes-closed stability strongly predict foot movement symmetry, emphasizing the need for targeted rehabilitation to improve gait and mobility.